Rings for the finger - Kunz, George Frederick, 1856-1932 (Salt Lake City, UT : Project Gutenberg, 2023)
"Rings for the Finger" by George Frederick Kunz is a detailed historical account written in the early 20th century. The work explores the significance of rings throughout history, focusing on their origins, usages, materials, and cultural symbolism, particularly in relation to love, engagement, and mourning rituals. This comprehensive volume is likely to appeal to readers interested in jewelry, history, and the intricate meanings associated with adornments. At the start of the book, the author sets out the purpose of his work, explaining that it aims to gather everything important regarding finger rings from ancient times to the present. Kunz discusses the obscure origins of rings, tracing their development from modified seals used in ancient Egypt to various forms utilized in different cultures, such as signet rings and wedding bands. He highlights the societal and spiritual significance attributed to these ornaments, while providing a glimpse into their decorative evolution, talismanic attributes, and the craftsmanship behind their creation. The opening chapters promise to delve into diverse themes$1 (Bincluding rings' uses in official contexts, religious ceremonies, and personal milestones$1 (Bindicating a rich exploration of both material and sentimental value attached to rings. (This is an automatically generated summary.)s
Release date is 2023-08-17
Peter Becker, Karin Spence and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: Rings; Rings -- Folklore